An Analysis of The Effects of Income, Financial Attitudes, and Financial Literacy on The Financial Well-Being of The Community in Dangin Puri Kelod Village, East Denpasar District - Stefany Tesalonika Benu; Agus Wahyudi Salasa Gama; I Gusti Ngurah Bagus Gunadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to analyze the influence of income, financial attitudes, and financial literacy on the financial well-being of the community in Dangin Puri Klod Village. Financial well-being issues persist in this area, as evidenced by low savings capacity, lack of emergency funds, consumptive behavior, and limited understanding of personal financial management. This study employs a quantitative approach using a survey method involving 170 respondents, and the data were analyzed using multiple linear regression via SPSS. The independent variables include income (X1), financial attitudes (X2), and financial literacy (X3), while the dependent variable is financial well-being (Y). The results indicate that income, financial attitudes, and financial literacy have a positive and significant impact on the financial well-being of the community. These findings confirm that the ability to manage income, cultivate appropriate financial attitudes, and improve financial literacy are crucial factors in achieving better financial well-being. This study is expected to contribute to the development of financial behavior research and serve as a reference for village governments, financial institutions, and the community in designing strategies to improve financial well-being through more effective financial education and planning.